Role of Teaching Learning Strategies in Academic Performance of Students During Covid-19 - Sidra Shahid; Dr. Wajiha Kanwal; Uroosa Rafaqat; Saba Farid (Journal of Management Practices, Humanities and Social Sciences, 2022)
This research is an attempt to explore the role of teaching learning strategies on academic performance of students during covid-19 in Tehsil Khanpur. The current research was separated into two sections. First section was based on first objective, related to explore the perception of secondary school teachers about the role of teaching learning strategies in students’ academic performance during Covid-19. Second section was based on second and third objective related to study variation in the application of teaching learning strategies in Covid-19 & to find out the effectiveness of applied teaching learning strategies on student performance. The target population of the study comprised male and female secondary school teachers. Sample of the study consisted of 50 male and female SSTs selected through convenient sampling technique. The study was descriptive in nature and data was collected through survey technique. Self-made questionnaire and semi structured interview were used as tool. The data was collected from secondary school teachers. SPSS was used to examine the collected data. Questionnaire data was analyzed using mean, standard deviation. After analyzed the questionnaire, researcher check the highest mean of that teaching learning strategy is extensively used in those school and then compare the BISE result with that extensively used strategy, because effectiveness of strategy and student performance are interlinked. This research was based on mixed method, using both quantitative and qualitative methods. It was found that online Teaching learning strategy is extensively used in maximum schools and it has a positive impact as students show outstanding performance in BISE Examination and this effect the student’s results. So, it must be continued in the future. Study indicates that teaching learning strategies are very important in education all setting as it affects the academic performance of the students.